MANAGEMENT OF INNOVATIONS AND CONFLICTS OF INTERESTS IN THE RUSSIAN TRANSPORT COMPLEX - A. S. Oleynikov (Модернизация, инновация, развитие, 2016)
Success of any innovation process depends, in part, on the management of conflicts of interests. The conflict of interest is regarded as availability with a decision-maker of a corruption interest that prevents realization of a society-important goal. Factors that make conflicts of interests andnegatively or positively influence the innovation process are discussed. Ways of minimizing negative impacts and instruments of managing the conflicts of interest are proposed for successful development of an innovative transport system. It is necessary to improve public procurementand tax legislations, to introduce in state institutions the key principles of solving issues related to conflicts of interest that are practiced by the Organization for Economic Cooperation and Development.